2015
DOI: 10.1007/s00408-015-9768-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA Mismatching on Survival in Lung Transplantation

Abstract: HLA mismatching is associated with increased hazard risk for death after LTx, while induction with basiliximab and other factors related to LTx reduce the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The importance of HLA matching has been reported in a number of large observational studies, including the 2017 ISHLT report, and a 23,000-patient study reported by Hayes et al (Fig. 1) [2,55]. It is worth noting that, while Hayes et al employed a lower cut-off for HLA mismatch (< 3 vs ≥ 3), their study actually reported a lower hazard ratio for mortality compared to the ISHLT report, which suggests that having three HLA mismatch may not be associated with significantly worse outcome.…”
Section: Antigenic Matchingmentioning
confidence: 89%
“…The importance of HLA matching has been reported in a number of large observational studies, including the 2017 ISHLT report, and a 23,000-patient study reported by Hayes et al (Fig. 1) [2,55]. It is worth noting that, while Hayes et al employed a lower cut-off for HLA mismatch (< 3 vs ≥ 3), their study actually reported a lower hazard ratio for mortality compared to the ISHLT report, which suggests that having three HLA mismatch may not be associated with significantly worse outcome.…”
Section: Antigenic Matchingmentioning
confidence: 89%
“…Chimerism and HLA compatibility are hypothesized to be involved in the favorable results of LDLLT after allo-HSCT. 3,13,14 The recipients of LDLLT following allo-HSCT from the same donor may require little or no immunosuppressive therapy. [13][14][15] It has been reported that the rate of PTLD, as a complication of LDLLT after allo-HSCT, was 10.5% in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…3,13,14 The recipients of LDLLT following allo-HSCT from the same donor may require little or no immunosuppressive therapy. [13][14][15] It has been reported that the rate of PTLD, as a complication of LDLLT after allo-HSCT, was 10.5% in Japan. 13 The incidence of de novo malignancy after lung transplantation, including PTLD, appeared to be higher in patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…21 Intriguingly, published studies have also provided conflicting evidence by demonstrating that the degree of HLA mismatching between donor and recipient may not impact lung allograft rejection. 2226 This indicates the possibility of alternate immune mechanisms in mediating lung allograft rejection. 27,28 Emerging data from our laboratories and others have implicated the role of autoimmunity against lung-restricted self-antigens in the development of rejection following lung transplantation.…”
Section: Introductionmentioning
confidence: 98%